Latihan Batuk Efektif pada Pasien dengan Pneumonia - Dwi Novitasari; Rizki Ayu Adiani Putri (Jurnal Sehat Mandiri, 2022)
Pneumonia is a disease that infects the respiratory tract and is accompanied by symptoms of cough and runny nose and shortness of breath caused by viruses, bacteria, and foreign substances. One of the interventions to expel phlegm is to practice coughing effectively independently. Effective coughing is a coughing exercise that aims to expel phlegm that is stuck in the patient's airway, which is done correctly will help expel phlegm to the maximum. This case study was conducted to determine the effectiveness of the implementation of an effective cough on sputum production in patients with pneumonia at Kardinah Hospital, Tegal. The research method used is a descriptive case study with a nursing care process approach. The study was conducted by purposive sampling with the following criteria: medical diagnosis of pneumonia, adult age, experiencing ineffective airway clearance nursing problems, RR>20 x/minute, and willingness to be a respondent, in the upper Edelweiss room. The results showed that the patient's respiratory rate before the implementation was 26 x/minute to 20 times per minute. In addition, giving effective coughing exercises for 3x24 hours has shown a change in the patient's ability to expel phlegm. This study concludes that coughing exercises can effectively reduce the patient's respiratory rate within the normal range, improve SPO2, and increase sputum output. It is recommended for nurses to be able to use effective coughing exercises on airway clearance disorders.